A orientação da teoria do crime no sistema normativo: Considerações sobre a evolução da dogmática penal - Sala, Francisco Bulhões (2019)
The scope of the present work is to identify within the normative system the elements of the crime, making, to that end, a parallel between the theory of the norm and the criminal dogmatic system. This work is relevant because of the assertion that dogmatics, in the current stage of history, has emphasized its pragmatic function as opposed to a pretended normative systematization. However, it cannot be forgotten that dogmatics, regardless of the function and cognitive limits attributable, always has as its object the legal norm. Thus, we present the evolution of the dogmatic method to verify the influxes that generate not only in the definition of crime, as an object of the Crime Theory, but also in the concept of the penal norm. Thus, by emphasizing the current function of criminal dogmatics and defining the legal-penal norm, the elements of the crime will be identified in the normative system